If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + -9 = -6x + -10 Reorder the terms: -9 + -5x = -6x + -10 Reorder the terms: -9 + -5x = -10 + -6x Solving -9 + -5x = -10 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -9 + -5x + 6x = -10 + -6x + 6x Combine like terms: -5x + 6x = 1x -9 + 1x = -10 + -6x + 6x Combine like terms: -6x + 6x = 0 -9 + 1x = -10 + 0 -9 + 1x = -10 Add '9' to each side of the equation. -9 + 9 + 1x = -10 + 9 Combine like terms: -9 + 9 = 0 0 + 1x = -10 + 9 1x = -10 + 9 Combine like terms: -10 + 9 = -1 1x = -1 Divide each side by '1'. x = -1 Simplifying x = -1
| 2(x+7)=0 | | 5x-7=x+25 | | 7X-2(5-4X)=9X-4(X+1) | | 5-10x=9x+20 | | 3(x-7)=2(x+5) | | 8x^2-33x= | | -6x-6-4x=74 | | y-2/5=-1/3 | | -2x+7+4x=11 | | m+5.2=2.2 | | x+8+3x=44 | | x+x+x=213 | | 45x7/9 | | 5+6x-2x=-43 | | 5x+4-2x=-2 | | 1+7x=-34 | | 24-2y=3+5y | | -3(x-5)+2=2(x+3)-4 | | 2y-3/5=1/2 | | 2(x+1)=-3(4x-3) | | 72x4/9 | | x^3-(2+3i)x^2-(2-3i)x^2+(4-9i^2)x-x^2+(2+3i)x+(2-3i)x-(4-9i^2)= | | 28+x*.20=98 | | 7-4x=47 | | 2x^2=4+6x | | 10+5a=-15a | | -15a=5a+10 | | 2t+3(1-2t)= | | 4x-2x=-3x+25 | | 9+1/3y=13 | | s+1.2=1.5 | | 1/5x+1/5x=10/11 |